Choice, consent and owning our bodies: a feminist analysis of the continuities and discontinuities of women’s control over their reproduction from apartheid to democracy in South Africa. - Odendaal, Inge (Stellenbosch : Stellenbosch University, 2023)
Thesis (MA)--Stellenbosch University, 2023.